Formulation Design And Evaluation Of Orally Disintegrating Tablets Of Loratadine Using Direct Compression Process - JAYADEV PATIL,; CHANDRASEKHAR KADAM,; VISHWAJITH V,; GOPAL.V, (International Journal of Pharma and Bio Sciences, 2011)
The present work aims to formulate and design orally disintegrating tablets containing antihistamines like Loratadine using different pharmaceutical compositions with simple manufacturing procedures to enhance patient compliance. Loratadine was formulated into orally disintegrating tablets by direct compression method using suitable excipients like Maltodextrin, Mannitol, Micro crystalline cellulose, combination of Mannitol with Starch, Croscarmellose sodium, Citric acid, Sodium bicarbonate along with Mint flavor, which were evaluated by using simple analytical techniques. The taste of the formulation was enhanced using artificial sweetener Aspartame and Mint flavour. The tablets were evaluated for weight variation, hardness, friability, drug content, wetting time and disintegration time along with in-vitro dissolution. It was observed that the direct compression process using commercial grades of excipients like combination of Mannitol with Starch and Micro crystalline cellulose as directly compressible diluents along with super disintegrants like Croscarmellose Sodium was found to be more promising to prepare orally disintegrating tablets.